Economic evaluations of onchocerciasis interventions: a systematic review and research needs. Issue 7 (9th May 2019) - Turner, Hugo C.; Walker, Martin; Pion, Sébastien D. S.; McFarland, Deborah A.; Bundy, Donald A. P.; Basáñez, María‐Gloria
Abstract: Objective: To provide a systematic review of economic evaluations that has been conducted for onchocerciasis interventions, to summarise current key knowledge and to identify research gaps. Method: A systematic review of the literature was conducted on the 8th of August 2018 using the PubMed (MEDLINE) and ISI Web of Science electronic databases. No date or language stipulations were applied to the searches. Results: We identified 14 primary studies reporting the results of economic evaluations of onchocerciasis interventions, seven of which were cost‐effectiveness analyses. The studies identified used a variety of different approaches to estimate the costs of the investigated interventions/programmes. Originally, the studies only quantified the benefits associated with preventing blindness. Gradually, methods improved and also captured onchocerciasis‐associated skin disease. Studies found that eliminating onchocerciasis would generate billions in economic benefits. The majority of the cost‐effectiveness analyses evaluated annual mass drug administration (MDA). The estimated cost per disability‐adjusted life year (DALY) averted of annual MDA varies between US3 and US30 (cost year variable). Conclusions: The cost benefit and cost effectiveness of onchocerciasis interventions have consistently been found to be very favourable. This finding provides strong evidential support for the ongoing efforts to eliminate onchocerciasis from endemic areas. Although these results are very promising, there are several important research gaps that need to be addressed as we move towards the 2020 milestones and beyond. Abstract : Objectif: Fournir une analyse systématique des évaluations économiques réalisées pour les interventions contre l'onchocercose, résumer les principales connaissances actuelles et identifier les lacunes de la recherche. Méthode: Une revue systématique de la littérature a été menée le 8 août 2018 en utilisant les bases de données électroniques PubMed (Medline) et ISI Web of Science. Aucune indication de date ou de langue n'a été appliquée aux recherches. Résultats: Nous avons identifié 14 études principales rapportant sur les résultats d'évaluations économiques d'interventions contre l'onchocercose, dont 7 étaient des analyses coût‐efficacité. Les études identifiées ont utilisé diverses approches pour estimer les coûts des interventions/programmes étudiés. A l'origine, les études ne mesuraient que les avantages associés à la prévention de la cécité. Progressivement, les méthodes se sont améliorées et ont également capturé les maladies de la peau associées à l'onchocercose. Les études ont montré que l'élimination de l'onchocercose générerait des milliards de bénéfices économiques. La majorité des analyses coût‐efficacité ont évalué l'administration annuelle en masse de médicaments (AMD). Le coût estimé par année de vie ajustée par rapport à l'incapacité (DALY) corrigé pour l'AMD annuelle varie entre 3 et 30 USD (variable de l'année de coût). ConclusionsLe rapport coût‐efficacité et la rentabilité des interventions contre l'onchocercose se sont toujours avérés très favorables. Cette constatation fournit un solide appui probant aux efforts en cours pour éliminer l'onchocercose des zones d'endémie. Bien que ces résultats soient très prometteurs, plusieurs lacunes importantes en matière de recherche doivent être comblées à mesure que nous nous approchons des étapes clés pour 2020 et au‐delà.